Immunisation of children by a nurse without a doctor present. Issue 6569 (14th February 1987) - Jefferson, N; Sleight, G; Macfarlane, A
Abstract : Over 16 months 148 children were referred by health visitors and general practitioners to a specially trained nurse for failing to complete courses of immunisation. A further 91 children of travellers' families were identified as needing immunisation. The nurse carried out 810 immunisations on 237 of these children in their homes without a doctor being present. There were only two refusals, and one child suffered a mild anaphylactic shock. The cost per immunisation, in nurse's salary and travel expenses, was pounds 8. This is an effective and fairly inexpensive way of achieving uptake of immunisation in such groups of children, and there seems no reason why trained nurses should not give immunisations either in a child health clinic or at home, without a doctor present.